Avaliação de Variáveis para Delimitação de Áreas Protegidas Costeiras e Marinhas: sugestão de limites para uma Unidade de Conservação costeira de Uso Sustentável na região das Reentrâncias Maranhenses (Estado do Maranhão, Brasil) - Fukuda, Juliana Cristina (2006)
The protected areas (PAs) for nature conservation are important tools for maintaining ecological function and biodiversity conservation in a determined region. Specific laws for their protection are applied in the defined space within their limits. Thus, considering boundaries definition as a characteristic of fundamental importance to reach the goals for which the protected area has been created, in this work we aimed to evaluate socioeconomic- cultural and environmental features, and also management and political variables for suggesting boundaries to a marine costal protected area (MCPA) in the Reentrâncias Maranhenses region, with special attention to the municipality of Porto Rico do Maranhão. This portion of coast is characterized for its high nutrients levels, macro-tidal regimes, large continental shelf and exuberant mangroves, and the artisanal fishing as the main economic activity. We limited the purpose of this study to the managed MCPAs. We used interviews, field observations, water and sediment samples and secondary information to reach the following goals: 1) survey on the MCPAs in Brazil, analysing the management difficulties answered by their managers related to the boundaries definition; 2) discussion whether to create a new protected area in the region and its advantages; 3) characterize the local fishery and the direct users of fishery resources; 4) make a list of vertebrates species (not including herpetofauna) and benthos species which have occurrence indication in the area; 5) classify the local environments based on orbital images and field work; 6) sample estuarine waters for physical and chemical analysis; 7) consider land tenure, fishery management and navigation safety issues. The main contributions of this work are: a) information on 141 publicly managed coastal and marine protected areas; b) confirmation that in the older protected areas there have been fewer studies on boundary definition, in inverse proportion to current occurrence of management problems. These studies have been more frequent in the Extractive Reserves than in the Environmental Protected Areas; c) indications of an unsustainable fishery, socially, economically and environmentally endangering the region; d) occurrence indication of 89 fish morphospecies, 25 of shore birds and 6 of mammals, emphasizing the ones in danger of extinction; e) elaboration and analysis of a multi-criteria matrix to indicate the most important environments for protection; f) indication of an ideal area for protection, only considering environmental concepts and indication of an area we believe would be the most suitable for a PA, considering the other management variables. Yet, this suggestion must be discussed with all the stakeholders, in a consistent effort to make aware and empower the users so that they realize that the conflicts and problems will only be minimized with stakeholder participation and commitment to the issue.